(untitled) (Journal of Nepal Physical Society, 2021)
Cold atmospheric pressure plasma technology has a variety of applications in different fields including material science and biomedical science. It has been using for surface modification and material processing in material science and used to improve the wettability, adhesion and biocompability of polymeric surfaces without altering the entire bulk properties. This paper outlines the characterization of cold atmospheric pressure plasma jet, which was generated in a high frequency (20 kHz) and high voltage (3.5 kV) power supply, as well as its application in the surface modification of high density polyethylene. Electrical and optical characteristics are used to estimate the electron density of the plasma. The effect of plasma on the surface properties of the material are analyzed by calculating contact angle, surface energy measurements and analyzing scanning electron microscopy images. Adhesive bonding strength and numerous other attributes have increased, however surface treatment is the process of cleaning, etching, functionalizing, and chemically treating substrates to improve roughness and adhesive properties on the surface. Cold plasma can induce a soft roughening on the surface through ion bombardment with polar functional groups resulting in the decrease in water contact angle.